THE INFLUENCE OF SPEAKING SKILLS TEACHING MATERIALS ON STUDENTS' LANGUAGE POLITENESS BASED ON THE MOTHER TONGUE - Sakinah Fitri; Muhammad Saleh (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Speaking skills and mother tongue are strongly suspected of having an influence on language politeness in communication. The study aims to investigate the implementation of teaching materials designed for speaking skills and students' understanding of language politeness based on their mother tongue. This research employs a pre-experimental method to examine the influence of speaking skills teaching materials on students' language politeness, taking into account their mother tongue at Universitas Negeri Makassar. The instruments used were pretest and posttest tests. It is intended to obtain an overview of individual factors, such as mother tongue , that affect the level of politeness of students in everyday communication. The results of the study show (1) that the implementation of speaking skills teaching materials has an influence on increasing language politeness. (2) The mother tongue has an influence on increasing student language politeness. Although the test results for the group of students with Indonesian mother tongue were higher (4.03) compared to the group of students with Makassar-Bugis mother tongue (3.91).